(untitled) (Research, Society and Development, 2020)
Fruit growing is a way to boost the economy of the Northeast. It is believed that the understanding of the chemical characteristics and nutritional value of fruits serves as a tool to propose improvements in the form of consumption and in the use of these foods. The exposed work aimed to evaluate the physical and chemical characteristics of tropical fruits sold in open markets in the city of Mossoró–RN. For this, pineapple, banana, mango and cashew fruits were purchased, these were cleaned and submitted to analyzes of pH, humidity, vitamin C, soluble solids and total soluble sugars. The results show that the analyzed fruits have an approximate pH value, with the average of the range between 3.9 – 4.2, showing that the fruits have an acid character. The moisture content varied between 81% and 71% for cashew and banana, respectively. The concentrations of vitamin C were quite variable, with cashew the most concentrated and pineapple the least, with an average of 49.5 and 17 mg of vitamin C/100 g of fruit, respectively. For soluble solids, pineapple and mango were the fruits with the highest concentration, however, when evaluated the total soluble sugars the banana is the fruit with the highest concentration. Therefore, it can be seen that tropical fruits had an excelente nutritional value and a high content of antioxidant compounds.